Light and scanning electron microscopy of the small intestine of young Malaysian village chicken and commercial broiler - Kadhim, Khalid Kamil; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Babjee, Shaik Mohamed Amin; Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2014)
The intestinal mucosa of the Malaysian village chicken (MVC) and commercial broiler breed (CBC) from day 1 to 20 post-hatch was examined by means of light and scanning electron microscopy. The results showed that the intestinal mucosa was highly developed on day 1 in CBC as compared to MVC in regard to villus height, crypt depth and thickness of tunica muscularis. At day 1 post-hatch, it was observed that the mid cecum of the CBC showed plicae with short villi, while very short villi without plicae were observed in MVC. The intestinal villi in both breeds had a finger-like shape at day-old chick and changed to plate-like and tongue-like shapes toward the end of the experiment for CBC and MVC, respectively. Unlike MVC, the surface epithelia of the intestinal villi in CBC exhibited cell activities represented by surface recesses, clear cell outline and dome-shaped cells with protuberances, while a marked corrugated surface and areas of discontinuities were dominantly seen on the intestinal villi of the MVC particularly on the ileal villi. This study revealed that the intestinal mucosa of MVC of newly hatched chick was less evolutionary as compared to CBC which showed earlier development and maturation with more active villi to provide the highest rate of absorption as the breed selected for high body weight and rapid growth rate.